Factors Affecting Dysfunctional Audit Behavior - Afly YESSIE (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study aims to test several hypotheses regarding the influence of turnover intention, performance auditor, organizational commitment, locus of control, Times budget pressure and professional commitment on dysfunctional audit behavior. This research was conducted on auditors working in the Public Accounting Firm (KAP) Jakarta region registered with the Indonesian Institute of Public Accountants (IAPI) in 2019 using the dissemination of questionnaires. The analytical instrument in this study is double regression. The results of this study indicate that turnover intention, performance audit, time budget pressure and professional commitment have a positive and significant effect on the dysfunctional audit behavior while the locus of control and organizational commitment negatively affect the dysfunctional audit behavior. This research contributes to the development of science, especially in the field of auditing the acceptance of dysfunctional audit behavior. The results of this study are also expected to be used by public accounting firms to consider when to hire new auditors so that companies can prefer those who have a high locus of control and have a high organizational commitment so that acceptance of dysfunctional audit behavior can be minimized.